2021
DOI: 10.3390/polym13183029
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Kartigen® in Treating Cartilage Defects: A Randomized, Controlled, Phase I Trial

Abstract: Here, we aimed to investigate the safety and preliminary efficacy of Kartigen®, a matrix with autologous bone marrow mesenchymal stem cell-derived chondrocyte precursors embedded in atelocollagen. As a surgical graft, Kartigen® was implanted onto the cartilage defects at the weight-bearing site of the medial femoral condyle of the knee. Fifteen patients were enrolled and stratified into two groups, undergoing either Kartigen® implantation (n = 10) or microfracture (control group, n = 5). The primary endpoint w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 66 publications
0
11
0
1
Order By: Relevance
“…Table 5 shows the MCMS scores from the 25 included studies. Six studies 10 , 20 , 21 , 28 , 30 , 31 received an excellent score, 17 studies 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 22 , 23 , 24 , 27 , 29 , 32 received a good score, and 2 studies 25 , 26 received a fair score.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 5 shows the MCMS scores from the 25 included studies. Six studies 10 , 20 , 21 , 28 , 30 , 31 received an excellent score, 17 studies 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 22 , 23 , 24 , 27 , 29 , 32 received a good score, and 2 studies 25 , 26 received a fair score.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies 8 , 10 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 reported on postoperative WB ( Table 2 ). All but 2 studies 16 , 17 allowed partial WB immediately after operation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If not treated in time, it will cause joint pain and movement disorder, eventually lead to osteoarthritis. 3 It is reported that people with knee cartilage injury are 7.4 times more likely to suffer from osteoarthritis than those without cartilage injury. 4 So far, the treatment methods for articular cartilage injury mainly include conservative treatment and surgical treatment.…”
Section: Introductionmentioning
confidence: 99%